2007
DOI: 10.3748/wjg.v13.i19.2747
|View full text |Cite
|
Sign up to set email alerts
|

Complications of high intensity focused ultrasound in patients with recurrent and metastatic abdominal tumors

Abstract: AIM:To analyze the local and systemic complications of high intensity focused ultrasound (HIFU) for patients with recurrent and metastatic abdominal tumors. METHODS:From Aug 2001 to Aug 2004, 17 patients with recurrent and metastatic abdominal tumors were enrolled in this study. Real-time sonography was taken, and vital signs, liver and kidney function, skin burns, local reactions, and systemic effects were observed and recored before, during, and after HIFU. CT and MRI were also taken before and after HIFU. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 23 publications
(26 reference statements)
0
51
0
1
Order By: Relevance
“…11 In other clinical applications of HIFU, skin burns and bowel infarction have been reported. 14,15 Morbidity needs to be assessed on a larger scale. Due to stringent inclusion criteria regarding TSH, the tight deadlines of this pilot study, and the subsequent lack of participants, patient enrollment had to be stopped.…”
Section: Discussionmentioning
confidence: 99%
“…11 In other clinical applications of HIFU, skin burns and bowel infarction have been reported. 14,15 Morbidity needs to be assessed on a larger scale. Due to stringent inclusion criteria regarding TSH, the tight deadlines of this pilot study, and the subsequent lack of participants, patient enrollment had to be stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-four studies reported on the clinical use of HIFU (7,(10)(11)(12)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) to treat liver lesions , while 19 series were found on HIFU treatment for pancreatic cancers (6,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73) and 4 studies included patients suffering from both liver and pancreatic cancers (74)(75)(76)(77), reporting on a total of 1,682 and 823 cases for the liver and pancreas, respectively. However, the real number of patients who benefited from HIFU treatment is much larger, since a recent review article from Zhou reported on over 3,000 cases of advanced pancreatic cancer treated with HIFU alone or in combination with chemotherapy (CHT) or radiotherapy (RT) (78).…”
Section: Study Selection and Level Of Evidencementioning
confidence: 99%
“…The most frequent complications were skin burns at the application sites and osteonecrosis of ribs or vertebra along the US pathway ( Tables 5,6). Post-HIFU pain was not assessed systematically and was reported in 17 studies (384 patients undergoing liver HIFU procedures) (7,12,(19)(20)(21)(22)24,26,28,29,32,39,41,45,49,54,75) and 6 studies (62 patients receiving HIFU for pancreatic malignancies) (56,59,62,70,71,75). In only a few of those trials, a semi-quantitative evaluation tool was used to report pain level, based on the analgesic requirements (mild = no analgesic; moderate = non-steroidal anti-inflammatory drugs; severe = required morphine) (7,19,20,24,39).…”
Section: Complicationsmentioning
confidence: 99%
“…In theory, the ablation beams target a specific region without damaging nearby structures. However, as reported in previous studies, HIFU induced skin burns and pain in the treatment region, neurapraxia of stomach and intestines, rarely developed superior mesenteric infarction and perforation in terminal ileum [4]. Jung et al [5] showed that the ultrasound heat could cause third-degree burn, necrosis of the ribs along the main ultrasound beam path, rib fractures and other complications such as biliary obstruction, pneumothorax and fistula formation.…”
Section: Introductionmentioning
confidence: 78%